2016
DOI: 10.1016/j.apcata.2016.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Silica material variation for the MnxOy-Na2WO4/SiO2

Abstract: The oxidative coupling of methane (OCM) is one of the best methods for the direct conversion of methane. Among the known OCM catalysts, Mn x O y-Na 2 WO 4 /SiO 2 is a promising candidate for an industrial application, showing a high methane conversion and C 2 selectivity, with a good stability during long-term catalytic activity tests. In the present study, some results have been already published and discussed briefly in our previous short communication [Yildiz 2014]. However, we herein investigated comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 52 publications
7
35
1
Order By: Relevance
“…Interestingly, all these catalysts exhibit similar and relative good catalytic performances for OCM reaction, suggesting that a little variation in composition and crystalline structure of Na−Mn−W−SiO 2 won't significantly change its catalytic performance. Previous study also reported that the MnWO 4 had no effect on the catalytic performance . Besides, the XRD patterns for used catalysts (Figure b) were very similar to those for fresh catalysts (Figure a) except the weakened Na 2 WO 4 peaks (2θ=12.8 o , 14.8 o , 16.7 o , 24.6 o , and 28.1 o etc.)…”
Section: Resultssupporting
confidence: 68%
“…Interestingly, all these catalysts exhibit similar and relative good catalytic performances for OCM reaction, suggesting that a little variation in composition and crystalline structure of Na−Mn−W−SiO 2 won't significantly change its catalytic performance. Previous study also reported that the MnWO 4 had no effect on the catalytic performance . Besides, the XRD patterns for used catalysts (Figure b) were very similar to those for fresh catalysts (Figure a) except the weakened Na 2 WO 4 peaks (2θ=12.8 o , 14.8 o , 16.7 o , 24.6 o , and 28.1 o etc.)…”
Section: Resultssupporting
confidence: 68%
“…It should also be noted here that, as previously stated in literature, it is very challenging to reach a conclusion whether the Mn2O3 (Bixbyite) or the Mn7SiO12 (Braunite) or both phases are present in the Mn-W-Na/SiO2 catalysts 77,78 . The highest intensity peak generated by these phases is at approximately Q = 2.31 Å -1 ((222) reflection for Mn2O3 and (224) reflection for Mn7SiO12).…”
Section: Xrd-ct Experiments During Ocm -Unpromoted Mn-na-w/sio2 Catalystmentioning
confidence: 64%
“…The introduced OCM reaction conditions induced important solid-state changes; the diffraction signal generated by the Mn2O3 / Mn7SiO12 phases is seen to be diminished while a new crystalline Mn phase identified as MnWO4 is formed 77 . This result shows that under very reducing environments (i.e.…”
Section: Xrd-ct Experiments During Ocm -Unpromoted Mn-na-w/sio2 Catalystmentioning
confidence: 99%
“…One of the reasons behind the deactivation of this family of catalysts has been previously suggested to be associated with the preparation method; catalysts prepared via the incipient wetness method have been shown to be prone to fast deactivation due to inhomogeneous distribution of the active components between the catalyst surface and bulk (higher concentration at the catalyst surface) 16 . However, as shown in previous studies, the stability of the catalyst can be improved by using a high surface area support or by applying different metal precursors [35][36][37] . It is interesting to note that previous studies suggest that the initial support material and the preparation of catalyst play an important role in the catalyst activity and stability despite the inevitable transformation of amorphous silica to crystalline phases, and thus decrease in surface area, at high temperatures 18,33,53 .…”
Section: Discussionmentioning
confidence: 96%
“…The authors reported that the silica support showed the best overall performance (selectivity/conversion trade off), however SiC, Fe 2 O 3 and TiO 2 were also suggested as promising candidates as supports. Further work by the same research group 37,38 focused on investigating the impact of different silica supports on the performance of Na-Mn-W/SiO 2 catalyst. Although all support materials seemed to yield similar specific surface areas for as-prepared Na-Mn-W/SiO 2 catalysts, a significant enhancement in performance for the OCM reaction was shown when the catalyst was supported on SBA-15 mesoporous silica (increase in C 2+ yield from 3 -4 % to 10 % with stability tests performed over 16 h time on stream).…”
Section: Introductionmentioning
confidence: 99%